Health inequalities, risky behaviours and protective factors in adolescents: an analysis of secondary survey data from the UK. (May 2019) - Currie, K.; Bray, I.
Abstract: Objective: Adolescents are at risk of developing detrimental health behaviours that will affect their adult health. The aim was to estimate prevalence of health risk behaviours (HRB), comparing young people (12–18 years old) in Wiltshire (UK) who are vulnerable (looked after children, special education needs and disabilities, young carers and military dependents) to those who are not vulnerable and assess whether these behaviours are associated with protective factors (e.g. friendship groups). Study design: Secondary analysis of cross-sectional survey data ( n = 4129). Methods: In total, 900 vulnerable young people were compared with 3229 non-vulnerable young people. Differences between the two groups were assessed using Chi-squared tests, and associations with possible protective factors were assessed using logistic regression (adjusting for confounding factors). Results: Vulnerable young people have a higher prevalence of smoking tobacco (15% vs 9%, P < 0.001), using cannabis (7% vs 5%, P = 0.03) and self-harming (16% vs 9%, P < 0.001) monthly or more compared with the rest of the Wiltshire adolescent population. Whilst vulnerable young people have many shared protective factors with non-vulnerable young people, there are also differences between the two groups. Conclusions: There are shared protective factors across HRB that can build on the resilience of a young person, impacting their current and future health. Therefore, we should focus our attention on developing protective factors that promote health and well-being, not solely delivering specialist interventions targeted at specific risks. Further consideration should be given to identifying and promoting protective factors specifically for vulnerable people as they have higher levels of HRB and experience protective factors differently. Highlights: Vulnerable young people experience higher prevalence of health risk behaviours. Shared protective factors are associated with reductions in multiple health risk behaviours. There is some evidence that vulnerable young people may respond differently to protective factors. Prevention strategies and interventions to reduce adolescent risk-taking behaviours should take this into account.